Social Security Guide : The White Paper and the Beveridge Report Compared - Great Britain. Office of the Minister of Reconstruction. Social insurance ; Great Britain. Inter-departmental Committee on Social Insurance and Allied Services. Social insurance and allied services ; Beveridge, William Henry Beveridge, Baron, 1879-1963; Clarke, Joan Simeon (London : The Social Security League)
1944-10-01 1944 1940s 20 pages for reading either. It is meant only to give selected comparisons which readers may like to have at hand. Classification The White Paper adopts the Beveridge classification of the population into six groups:— Class I: Employees. Class II: Others gainfully occupied. Class III: Housewives. Class IV: Others of working age not gainfully occupied. Class V: Children below working age. Class VI: Persons retired and above working age. There will be no excepted categories. Weekly contributions will be registered by a single stamp stuck on the contributor's card. Contributions Adult Weekly Contributions Compared Class I. Class II. Class IV. Insured Person Employer W. P. B R. W. P. B. R. W. P. B. R. W. P. B. R. Men 3/10 4/3 3/1 3/3 4/2 4/3 3/4 3/9 Women 3/- 3/9 2/5 2/6 3/6 3/9 2/8 3/- W.P.: White Paper. B.R.: Beveridge Report. The White Paper adult rate starts from 18, Beveridge from 21. White Paper juvenile rates are payable by those aged 16-18. Beveridge has separated rates for those aged 16-17 and 18-20. For this reason juvenile rates are not here compared. Benefits Similarities The following weekly benefit rates are the same under both schemes: — Unemployment and Sickness*:— Single persons 24/- Man with wife not gainfully occupied ....................................40/- Married woman gainfully occupied ................................................16/- Dependant's allowance 16/- Maternity benefit for 13 weeks to normally gainfully occupied women 36/- Widows benefit for 13 weeks 36/- Guardians benefit 24/- The following grants are also the same under both schemes: — Maternity £4 Death: — Adult (W.P.: over 18; B.R.: over 20) £20 Aged under 3 £6 Intermediate age groups, differently divided in the two schemes .......................................... £10 and £15 Differences The Beveridge Report also recommends a marriage grant payable to insured women, up to £10. This the White Paper omits. As already noted, the White Paper suggests Children's Allowances at *NOTE.— The White Paper fixes invalidity benefit (payable after sickness benefit has been received for three years at:— Single 20/- ; Double 35/- ; Married woman 16/- (No change); Dependant 15/-. 12 15X/2/453/3